Improving Employee Performance: Assessment of Leadership Style, Work Environment, and Work Motivation Aspects - Suwignyo Widagdo; Domingos Lemos Lopes; Helmi Agus Salim (ABM: International Journal of Administration, Business and Management, 2023)
This study aims to examine the influence of leadership style, work environment and work motivation on employee performance at the Ijen sub-district office, Bondowoso district. The research data were obtained from distributing questionnaires to research objects with a sampling technique using saturated sampling. This type of research is quantitative. The respondents in this study were all employees at the Ijen sub-district office, Bondowoso district, totaling 30 people with details of 25 people with civil servant status and 5 people with contract worker status. Data analysis in this study used Validity Test, Reliability Test, t-test, F Statistic Test, Determination Coefficient. The results of this study indicate that leadership style, work environment and work motivation have a significant effect partially or simultaneously on employee performance, this is evidenced by the t count value> t table and the F count test value> F table. The coefficient of determination of 0.831 indicates that 83.1% of employee performance variations can be explained by the three variables